2017
DOI: 10.1093/mnras/stx2194
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the contribution of active galactic nuclei to reionization

Abstract: Recent results have suggested that active galactic nuclei (AGN) could provide enough photons to reionise the Universe. We assess the viability of this scenario using a seminumerical framework for modeling reionisation, to which we add a quasar contribution by constructing a Quasar Halo Occupation Distribution (QHOD) based on Giallongo et al. observations. Assuming a constant QHOD, we find that an AGN-only model cannot simultaneously match observations of the optical depth τ e , neutral fraction, and ionising e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 80 publications
(113 reference statements)
7
46
0
1
Order By: Relevance
“…Following Giallongo et al (2015) and MH, a number of authors have revisited the question of the importance of non-stellar sources during hydrogen reionization (e.g. D' Aloisio et al 2017a;Upton Sanderbeck et al 2016;Chardin et al 2017;Onoue et al 2017;Kulkarni et al 2017;Qin et al 2017;Mitra et al 2018;Hassan et al 2018). However, these analytic or semi-numerical studies do not include a detailed treatment of radiation transfer which is necessary to make more accurate predictions (especially for the temperature of the IGM) and produce realistic synthetic observations to be compared with actual data.…”
Section: Introductionmentioning
confidence: 99%
“…Following Giallongo et al (2015) and MH, a number of authors have revisited the question of the importance of non-stellar sources during hydrogen reionization (e.g. D' Aloisio et al 2017a;Upton Sanderbeck et al 2016;Chardin et al 2017;Onoue et al 2017;Kulkarni et al 2017;Qin et al 2017;Mitra et al 2018;Hassan et al 2018). However, these analytic or semi-numerical studies do not include a detailed treatment of radiation transfer which is necessary to make more accurate predictions (especially for the temperature of the IGM) and produce realistic synthetic observations to be compared with actual data.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work indicates that as much as 20% of all ionizing photons may have needed to escape from star-forming galaxies in order to fill out the necessary budget for cosmological reionization (Robertson et al 2015), although complementary analyses have indicated that values as low as 4-6% may be sufficient (Hassan et al 2015;Kulkarni et al 2013). If the higher number is correct, then it introduces tension with measurements of fesc, which tend to favor fractions of 10% or less both at z ∼ 3 (Schaye 2006;Grazian et al 2015;Siana et al 2015) and locally (Bergvall et al 2006;Leitet et al 2013;Borthakur et al 2014;Izotov et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this model, reionization is assumed to be driven by two types of sources: (i) Pop II stars with a Salpeter IMF in the mass range 1-100 M , and (ii) quasars. Although at lower redshifts quasars have been considered as significant ionizing sources, they have negligible contribution to the UV ionizing background at z 6 (D' Aloisio et al 2017;Mitra et al 2018a;Hassan et al 2018; but also see Madau & Haardt 2015;Khaire et al 2016 for QSO-driven reionization models). The model incorporates the QSO contribution by computing their ionizing emissivities based on the observed luminosity functions at z < 6 (Hopkins et al 2007).…”
Section: Modeling Cosmic Reionizationmentioning
confidence: 99%